Jews and Christians in the Roman World: from historical method to cases - Mason, Steve (Ancient Judaism and early Christianity, 2023)
Scholars bring a plethora of methods to the study of ancient Judaea and Christian origins. Applying principles of historical method to questions ranging from the Flavian triumph to the Essenes and the apostle Paul, this study argues that method matters.